Um mundo feito de ferro: a lírica de Drummond e Bob Dylan - Fernando Baiao Viotti (2018)
This dissertation is a comparative study focused on the poems of Carlos Drummond de Andrade and on the songs of Bob Dylan. Among the more important authors of the twentieth century on their respective languages, Drummond and Dylan have built prolific works in dialog with the major tendencies of modern lyric and with ancient poetic tradition as well. Starting with the analysis and interpretation of poems and songs, I try to identify similarities in the formal procedures and in the main issuesof both works, that can put together these two apparently much different authors. Drummond and Dylan came from small ore mining towns, and this common experience has great relevance to their works; ore is a symbolical presence in their lyrics, as a block to build their world´s perspective and also to develop specific poetical processes. The way as the poetic language of both authors projects the notion of a fractured self, an important question within literary and philosophical studies, is the subject of the last chapter. Considering the nature of the study, my comparison between a Brazilian poet and an American songwriter includes the discussion of the border-crossing between popular culture and high culture, the statute of song as a genre in face of literature, theplace of both works on the Brazilian and American cultural contexts and the relation between these contexts.